A useful method to keep azygos arch in minimally invasive resection of esophageal leiomyoma - Yu, Shaobin; Chen, Shuchen; Han, Ziyang; Chen, Sui; Chen, Mingduan; Lin, Jinghong; Huang, Shijie; Gao, Lei; Kang, Mingqiang (Journal of Thoracic Disease, 2017)
Lifting azygos arch with a prolene line is a useful way to keep azygos arch in minimally invasive resection of esophageal leiomyoma without affecting surgical exposure and operative procedure.